Changing epidemiology of vancomycin-resistant Enterococcus faecium: Results of a genome-based study at a regional neurological acute hospital with intensive care and early rehabilitation treatment - Linda Falgenhauer; Ingeborg Preuser; Can Imirzalioglu; Jane Falgenhauer; Moritz Fritzenwanker; Dietrich Mack; Christoph Best; Ursel Heudorf; Trinad Chakraborty (Elsevier, 2021)
Summary: Background: Vancomycin-resistant Enterococcus faecium (VREfm) are an emerging threat worldwide. In Germany, a VRE-belt with higher VREfm prevalences transversing its central east-west axis and including the state of Hesse was previously described. Recently, we detected a predominant VREfm clone in hospitals throughout the Rhine-Main metropolitan area of Hesse. Aim: Here we expanded our study on VREfm to a regional neurological acute hospital outside of the metropolitan area with patient referrals from throughout Hesse and the neighboring federal state of Rhineland-Palatinate. Material/Methods: VREfm isolates obtained between 2016-2018 from a regional neurological acute hospital with intensive care and early rehabilitation units were investigated (n=55). Patient data was collected and analyzed together with whole-genome sequencing data to investigate antibiotic resistance and virulence determinants of the VREfm. The population structure of VREfm was investigated using the Core genome-based multilocus sequence typing (cgMLST). Findings: The average age of the patients was 67.1 years. For 96% of the patients, a previous hospital stay was reported. 64% of the patients were treated with antibiotics. All VREfm harbored the vanB vancomycin resistance gene. The multilocus sequence types (STs) detected changed abruptly from four different STs in 2016 to a predominant ST in 2017 and 2018 (ST117). Most of the ST117 isolates were members of the cgMLST type CT71. Conclusion: The results indicate a sudden shift of the VREfm population structure from a semi-heterogeneous population to a pre-dominant clone within an interval of two years. Further investigations are warranted to understand the epidemiology and emergence of this clone.